NEW DRIVERS: FIRST YEAR OF DRIVING EXPERIENCE AND THEIR CRASH RATES - Laberge-Nadeau, Claire; Maag, Urs; Dionne, Georges; Desjardins, Denise; Messier, Stéphane (Assurances, 1997)
The main objective of this research is to characterize patterns of new drivers' crash rates per 30 day periods over one year after obtaining the first driving permit. The data set contains the individual records for all the new licensees from the province of Quebec who started the process of acquiring a license between March 1, 1989 and February 28, 1993, two years before and after the reform of March 1, 1991 which changed the rules of access to a first driving license. To have comparable groups, the candidates had to succeed in obtaining the license within 270 days of obtaining the learner's permit, and the driving record had to be available for a full year following licensing.The accident distribution was modeled by a logistic regression since the monthly probability to be involved in more than one accident is very low. Men and women were analyzed separately as the average crash rate for women was about half the one for men. The models show that: 1) age affects significantly the crash rates for men and women; 2) experience reduces crash rates particularly over the first four months after licensing; 3) those who pass the theory exam in the first attempt (both genders) have lower crash rates; 4) but the reform had no direct effect on crash rates. New licensees constitute a heterogeneous group (age, sex) in terms of crash rates even though the law and the regulation were applied uniformly before the 1997 reform.